3D Measurement of Paralyzed Larynx in Japanese Using Cone Beam CT. (23rd August 2013) - Yabe, Haruna; Saito, Koichiro; Uno, Kosuke; Momoshima, Suketaka; Ogawa, Kaoru
Abstract : Objectives: Precise measurement of human organs with an error by less than one millimeter was realized by cone beam computed tomography (CBCT) imaging technology. The purpose of this study was to measure the shape/size of paralyzed larynges in Japanese patients with multiple parameters using CBCT. Methods: Eighty‐nine Japanese patients who referred to our institution with unilateral vocal fold paralysis from April 2007 to November 2011 were incorporated in this case series study. There were 54 males and 35 females, and the mean age was 59.9 years. Laryngeal CBCT images were taken in 2 conditions: 1) patients sitting relaxed (R image), and 2) patients applying pressure at their diaphragm (P image). Lengths of bilateral vocal folds, bilateral horizontal glottal angles, and sizes of gaps from a median plane of each larynx were measured in R images. Vertical gaps of bilateral vocal folds were measured in P images. Results: Mean lengths of non‐diseased vocal folds (males, 18.5 mm; females, 12.9 mm) were significantly longer compared with diseased side (males, 17.7 mm; females, 12.4 mm) in both males ( P =0.011) and females ( P = 0.001). Glottal angles were significantly wider in no diseased side (16.1°) compared with diseased side (9.4°, P = 0.0011). Vertical gaps were normalized with the lengths of non‐diseased vocal folds with mean value of 0.057. Conclusions: Our study showed the first correct measurement of paralyzed larynx in live Japanese patients. These data will contribute to the improvement of diagnosis and surgical procedures for the patients with laryngeal paralysis in the future.